Separation of pathogenic bacteria by chain length - Beech, Jason P. (2018)
Using Deterministic Lateral Displacement devices optimized for sensitivity to particle length, we separatesubpopulations of bacteria depending on known properties that affect their capability to cau se disease(virulence). For the human bacterial pathogen Streptococcus pneumoniae, bacterial chain length and the presence of a capsule are known virulence factors contributing to its ability to cause severe disease.Separation of cultured pneumococci into subpopulations based on morphological type (single cocci,diplococci and chains) will enable more detailed studies of the role they play in virulence. Moreover, wepresent separation of mixed populations of almost genetically identical encapsulated and non-encapsulated pneumococcal strains in our device.